Breastfeeding in the Community—How Can Partners/Fathers Help? A Systematic Review - Ogbo, Felix Akpojene (Int J Environ Res Public Health, 2020)
Support from partners/fathers and families can play a significant role in a mother’s decision to initiate, continue or cease breastfeeding postnatally. This study systematically reviewed published studies to determine the impact of specific types of partner support on breastfeeding initiation, duration and exclusivity. We used the 2015 Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines for the review. Seven computerized bibliographic databases (Embase, ProQuest Central, Scopus, PsycINFO, Web of Science, MEDLINE/PubMed and CINAHL) were searched. Of a total of 695 articles retrieved from the databases, seven studies met the inclusion criteria and reported on breastfeeding initiation, duration and exclusivity. Four of the seven studies found that partner support in the form of verbal encouragement to new mothers increased breastfeeding duration and exclusivity. Other types of partner supportive actions that led to improved breastfeeding behavior included sensitivity of the partner to the nursing mother’s needs, assistance in preventing and managing breastfeeding difficulties, and helping with household and child care duties. This review showed that specific supportive actions of partners/fathers in the community positively improved breastfeeding practices. To maximise the impact of breastfeeding policies and interventions among new mothers, breastfeeding programmes should consider the involvement of partners/fathers and their specific roles.